Menganalisis Budaya Belajar Siswa Di Pesantren - Yuris, Evi Cenna; Perangin Angin, Sri Levinia; Widiastuti, Indar; Lubis, Nurhalimah; Samosir, Indah Sucita; Selina, Nurul (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to analyze how students’ learning culture develops within the pesantren (Islamic boarding school) environment. Pesantren is a unique Islamic educational institution that not only teaches religious knowledge but also shapes character and builds students' discipline through an orderly and religiously nuanced lifestyle. The method used in this research is qualitative with a case study approach conducted at a pesantren in Central Java. To collect data, the researcher conducted observations, interviews, and gathered various related documents. The findings show that the learning culture in the pesantren is strongly influenced by religious values, discipline, and the active role of the kyai (religious leader) and ustadz (teacher) in guiding the students. A supportive learning environment and a structured study schedule also have a positive impact on students’ motivation and learning ethic. The study concludes that the learning culture in pesantren significantly contributes to shaping students’ personalities and academic achievements.